Efficacy of Hormonal Protocols on Haematological and Micro-minerals Parameters in Postpartum Anestrus Cows - Patil, Anil Dinkarrao; Belure, Virbhadra Suryakant; Razzaque, Waquar Ahmad; Bhikane, Anil Udhavrao; Gaikwad, Nandkumar Zatingrao; Dongre , Vilas; Alai , Rakesh (The Indian Journal of Animal Reproduction, 2023)
Thirty six post partum anestrus cows were selected for the present research work. Group I (n=12) were treated with CIDR based protocols and Group II (n=12) were administered Ovsynch protocol and Group III (n=12) was kept as a untreated control. In Group I, II and III the values of Hematological parameters like Hb (9.00±0.17, 9.15±0.15 and 8.65±0.30, 8.66±0.20, 8.73±0.20 and 8.25±0.20, 7.76±0.16, 7.69±0.32 and 8.18±0.18 g/dl) RBC (7.28±0.37, 9.15±0.15 and 8.65±0.30, 7.20±0.38, 8.73±0.20 and 8.25±0.33, 5.77±0.32, 7.69±0.32 and 8.18±0.18 x1012/l) and TLC 10.36±0.26, 10.49±0.25 and 9.77±0.40, 9.67±0.28, 9.90±0.47 and 8.08±0.57, 8.29±0.53, 7.98±0.54 and 8.63±0.44 x109/l) on Day 0, 7 and 25 were recorded in Group I, II and III, respectively. Microminerals parameters (μg/dl) like Iron (147.9±4.44, 147.9±4.44 and 150.1±7.84, 143.4±4.5, 158.2±4.65 and 149.4±7.71, 118.6±3.23, 118.6±3.12 and 118.4±3.04) Cobalt (1.8±0.14, 2.2±0.10 and 1.99±0.11, 1.7±0.10, 2.1±0.08 and 1.74±0.13, 1.6±0.12, 1.5±0.10 and 1.6±0.11) Copper (0.65±0.02, 0.78±0.03 and 0.71±0.04, 0.63±0.01, 0.77±0.03 and 0.69±0.03, 0.64±0.02, 0.63±0.02 and 0.65±0.02) and Zinc (87.6±1.18, 104.9±2.00 and 96.4±3.27, 86.7±1.22, 104.7±2.02 and 93.6±2.51, 85.5±1.03, 85.6±1.02 and 86.5±0.92) on Day 0, 7 and 25 were recorded in Group I, II and III, respectively. It can be concluded that the use of different hormonal protocols in postpartum anestrus cows has shown different effects on haematological and micro-minerals parameters.